Persistence, adherence, and all-cause healthcare costs in atazanavir- and darunavir-treated patients with human immunodeficiency virus in a real-world setting. (2nd April 2016) - Farr, Amanda M.; Johnston, Stephen S.; Ritchings, Corey; Brouillette, Matthew; Rosenblatt, Lisa
Abstract: Objectives: Atazanavir (ATV) and darunavir (DRV) are protease inhibitors approved for HIV treatment in combination with ritonavir (/r). The objectives of this study were to compare persistence (time to treatment discontinuation/modification), adherence, and healthcare costs among patients with human immunodeficiency virus (HIV) initiating ATV/r or DRV/r. Methods: This retrospective cohort study used commercial and Medicaid administrative insurance claims data. Patients initiating ATV/r or DRV/r from 2006–2013 with continuous enrollment for ≥6 months before and ≥3 months after initiation were included. Patients were followed from initiation until discontinuation/modification (≥30 day gap in ATV or DRV or initiation of a new antiretroviral medication), during which time adherence (proportion of days covered [PDC], with PDC ≥80% or 95% considered adherent) and per-patient per-month (PPPM) total healthcare costs were measured. DRV/r patients were propensity score matched to ATV/r patients at a 1:1 ratio to achieve balance on potentially confounding demographic and clinical factors. Commercial and Medicaid samples were analyzed separately, as were antiretroviral (ART)-naïve and experienced patients. Results: The final samples comprised 2988 commercially-insured and 1158 Medicaid-insured patients. There were no significant differences in hazards of discontinuation/modification between the ATV/r or DRV/r cohorts. With respect to odds of being adherent, the only marginally significant result was comparing odds of achieving PDC ≥80% among ART-naïve Medicaid patients, which favored ATV/r. All other adherence comparisons were not significant. Although ATV/r cohorts tended to have lower PPPM costs, the majority of these differences were not statistically significant. Conclusions: Patients with HIV treated with either ATV/r or DRV/r had similar time to treatment discontinuation/modification, adherence, and monthly healthcare costs. Results were similar across the pre-specified sub-groups. These findings are useful not only as an insight into clinical practice, but also as a resource for healthcare providers and payers evaluating treatment options for HIV+ individuals.